Industrial Agglomeration and Location Choice in Services and Retail Sector: The Case of India - Devesh Singh; Zoltán Gál (DETUROPE)
Behind the selection of location choices for services and retail sector, many factors work in conjunction. This research tried to determine which factors had an influence on location choice and agglomeration and which factors worked together to decide the location choice. This study empirically tests location determinant hypothesis. Our findings suggested that infrastructure, corruption and law, labour law and workforce had a significant effect on location choice. Other factors such as trade regulation, competition, sales and supply, access to land and permit, access to finance, institutional administration and political constraint had the insignificant effect on location choice. Our research used the 2014 World Enterprise Survey data from World Bank, and it included the 2116 registered companies sample responses.